Effect of Docosahexaenoic Acid on Ca(2+) Signaling Pathways in Cerulein-Treated Pancreatic Acinar Cells, Determined by RNA-Sequencing Analysis - Kim, Suhn Hyung (Nutrients, 2019)
Intracellular Ca(2+) homeostasis is commonly disrupted in acute pancreatitis. Sustained Ca(2+) release from internal stores in pancreatic acinar cells (PACs), mediated by inositol triphosphate receptor (IP3R) and the ryanodine receptor (RyR), plays a key role in the initiation and propagation of acute pancreatitis. Pancreatitis induced by cerulein, an analogue of cholecystokinin, causes premature activation of digestive enzymes and enhanced accumulation of cytokines and Ca(2+) in the pancreas and, as such, it is a good model of acute pancreatitis. High concentrations of the omega-3 fatty acid docosahexaenoic acid (DHA) inhibit inflammatory signaling pathways and cytokine expression in PACs treated with cerulein. In the present study, we determined the effect of DHA on key regulators of Ca(2+) signaling in cerulein-treated pancreatic acinar AR42 J cells. The results of RNA-Sequencing (RNA-Seq) analysis showed that cerulein up-regulates the expression of IP3R1 and RyR2 genes, and that pretreatment with DHA blocks these effects. The results of real-time PCR confirmed that DHA inhibits cerulein-induced IP3R1 and RyR2 gene expression, and demonstrated that DHA pre-treatment decreases the expression of the Relb gene, which encodes a component of the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) transcriptional activator complex, and the c-fos gene, which encodes a component of activator protein-1 (AP-1) transcriptional activator complex. Taken together, DHA inhibits mRNA expression of IP3R1, RyR2, Relb, and c-fos, which is related to Ca(2+) network in cerulein-stimulated PACs.